Influence of peanut skin extract on shelf-life of sheep patties - Paulo Eduardo Sichetti Munekata (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To evaluate the phenolic profile and antioxidant activity in vitro of peanut skin extract (PSE) and effect of PSE on characteristics of sheep patties during storage. Methods: PSE phenolic profile was evaluated in LC–MS analysis and by total phenolic content, 1,1-diphenyl-2-picrylhydrazyl radical scavenging capacity and ferric reducing/antioxidant power. Patties elaborated with sheep meat were packaged in modified atmosphere and storage at (2 ± 1) °C. The analyses were performed every 5 days for 20 days on microbial counts, physico-chemical properties, lipid oxidation, protein stability and sensory characteristics. Results: The major group of phenolic compounds in PSE was the proanthocyanidins followed by other flavonoids, which are related to potential phenolic content and antioxidant activity. The addition of PSE and butyl hydroxytoluene (BHT) reduced the microbial counts during the storage time, caused reduction on the loss of redness and sensory properties over time. The lipid and protein oxidation in sheep patties was effectively inhibited by PSE and BHT. Conclusions: The present results showed the potential application of PSE as a natural alternative to replace synthetic antioxidants (BHT) for increasing the quality and extending the shelf-life of sheep patties.